Through Hardship to the Stars - N. S. Konstantinova (Ибероамериканские тетради, 2023)
The article is devoted to one of the brightest phenomena of Brazilian culture – theater, which, for a number of objective reasons, is much less known abroad than its other areas. The genesis and main stages of the evolution of the dramaturgy and theatrical art of Brazil over the course of five centuries of its existence are briefly considered. The extremely important role of the Week of Modern Art, held in Sao Paulo in 1922, which marked the birth of Brazilian modernism, which radically influenced the entire subsequent cultural process, is emphasized. Particular attention is paid to the formation and development of the democratic tradition that has dominated the Brazilian theater since its inception to this day. The phenomenon of the «new theater» in various forms of its manifestation is considered. The theatrical theory and practice of one of the charismatic figures of the Brazilian culture of the 20th century, Augusto Boal, is analyzed. Attention is focused on the names of the country’s most famous playwrights, and as an example, some of the most striking theatrical productions that are firmly included in the «golden fund» of national culture are analyzed.